Fecal microbiota changes with fermented kimchi intake regulated either formation or advancement of colon adenoma - Park, Jong Min (J Clin Biochem Nutr, 2021)
Gut bacteria might contribute in early stage of colorectal cancer through the development and advancement of colon adenoma, by which exploring either beneficial bacteria, which are decreased in formation or advancement of colon adenoma and harmful bacteria, which are increased in advancement of colon adenoma may result in implementation of dietary interventions or probiotic therapies to functional means for prevention. Korean fermented kimchi is one of representative probiotic food providing beneficiary microbiota and exerting significant inhibitory outcomes in both APC/(Min+) polyposis model and colitis-associated cancer. Based on these backgrounds, we performed clinical trial to document the changes of fecal microbiota in 32 volunteers with normal colon, simple adenoma, and advanced colon adenoma with 10 weeks of fermented kimchi intake. Each amplicon is sequenced on MiSeq of Illumina and the sequence reads were clustered into Operational Taxonomic Units using VSEARCH and the Chao Indices, an estimator of richness of taxa per individual, were estimated to measure the diversity of each sample. Though significant difference in α or β diversity was not seen between three groups, kimchi intake significantly led to significant diversity of fecal microbiome. After genus analysis, Acinobacteria, Cyanobacteria, Clostridium sensu, Turicibacter, Gastronaeophillales, H. pittma were proven to be increased in patients with advanced colon adenoma, whereas Enterococcua Roseburia, Coryobacteriaceau, Bifidobacterium spp., and Akkermansia were proven to be significantly decreased in feces from patients with advanced colon adenoma after kimchi intake. Conclusively, fermented kimchi plentiful of beneficiary microbiota can afford significant inhibition of either formation or advancement of colon adenoma.